Photoluminescence Properties of Layered Perovskite-Type Strontium Scandium Oxyfluoride Activated With Mn4+ - Kato, Hideki; Takeda, Yohei; Kobayashi, Makoto; Kobayashi, Hisayoshi; Kakihana, Masato (Frontiers in Chemistry, 2018)
In this research, we have found that layered perovskite titanate Sr2TiO4 doped with Mn4+ exhibits photoluminescence even at room temperature despite no luminescence from Mn4+-doped SrTiO3 with a three-dimensional bulky perovskite structure. The relative position of t2g orbital of Mn to the valence band is a key factor for appearance of Mn4+-emission in Sr2TiO4:Mn. This result suggested usefulness of layered perovskite-type materials as hosts for Mn4+-activated phosphors than the bulky perovskite-type materials. Our investigation into photoluminescence of Mn4+-doped layered perovskite compounds has revealed that strontium scandium oxyfluoride Sr2ScO3F activated with Mn4+ exhibits Mn4+-emission with a peak at 697 nm under excitation at 300–600 nm and its emission intensity is much stronger than that of Sr2TiO4:Mn. The internal and external quantum yields of Sr2ScO3F:Mn were determined to be 50.5 and 43.5% under excitation at 345 nm, respectively.